UPAYA PENCEGAHAN TINDAKAN BULLYING ANAK MENGGUNAKAN KARTU KEGIATANKU - Nopi Nurul Hasanah; Ghina Wulansuci (IKIP Siliwangi, 2021)
This study aims to describe the efforts to prevent bullying in children in the school environment using the